Marketing Mix Analysis at Sapphire City Park Sumedang - Siti Zenab Nuraeni; Yayat Ginanjar; Zulkipli M Ridwan (Universitas Sebelas April, Fakultas Ekonomi dan Bisnis, 2022)
In its development, Sapphire City Park needs business, especially in terms of marketing related to products and promotions. The data analysis used in this research is descriptive analysis, and uses data collection techniques through observation, interviews and documentation. The product mix width includes 3 kinds of products offered. The length of Sacipa's product mix has more than 50 menu choices which are divided into 3 types, namely western, kasundaan and archipelago. The depth of Sacipa's product mix has resulted in developments including catering and decoration. The consistency of Sacipa's product mix is very concerned about product quality and service so that consumers feel satisfied. Advertising (advertising) used is through social media Instagram, Tiktok and using market places such as Go Food and Grab food. The company's personal selling uses interactive communication such as holding quizzes that aim to increase customer attractiveness and maintain good relationships with customers to create repeat purchases. Sales promotion (sales promotion) issues a new product every 3 months which can be considered as a limited edition product. Public relations (publicity) that Sacipa does is maintaining good relations with local residents, the authorities and all relevant shareholders. For direct marketing (direct sales) the company uses sales calls usually only for official business because they often use meeting room facilities. A good product mix and promotion can increase sales of Sapphire City Park.